Deformation characteristics and initiation mechanism of the Lijie landslide, Zhouqu, China - Gao, Jingxuan; Zhang, Nan; Cui, Xueliang; Wang, Lichao; Wang, Wenpei; Li, Ruidong (Frontiers in Earth Science, 2025)
The Lijie landslide in Zhouqu County, China, located within the tectonically active Bailong River Basin on the northeastern Qinghai-Tibet Plateau, exemplifies a high-elevation shear-out landslide controlled by faults with cascading hazard potential. This study employed an interdisciplinary methodology that integrated field surveys, drilling, geophysical prospecting, and deep displacement monitoring to determine the landslide’s deformation characteristics and initiation mechanisms. The results demonstrate a spatially heterogeneous deformation concentrated along the eastern margin and leading edge of the landslide source area. The key surface manifestations include interconnected tension cracks, road displacement, and localized collapse at the rear scarp and frontal zones. The F3 fault zone traversing the mid-upper slope induces intense rock mass fragmentation, whereas hydrogeological interactions between karstified Devonian limestone aquifers and impermeable Silurian slate aquitards facilitate groundwater accumulation within the fault zone, significantly reducing geomechanical strength. These factors govern the landslide’s progressive deformation and ultimate failure. Under coupled endogenic and exogenic dynamics, fault-controlled landslides in active orogens, such as the example from the present study, are prone to triggering large-scale compound hazard chains with amplified destructive potential, including landslide-debris flows and river blockage events.